E-book aggregators: new services in electronic publishing (Libellarium: journal for research in the field of information and related sciences, 2015)
This paper provides the results of the case study conducted on a sample of 17 websites that identify themselves as e-book aggregators, five platforms for content publishing and 16 websites that present themselves as e-book distributors. While conducting the case study, the answers were sought to the questions about location of website, its owners, activities, distribution channels, services, partners, languages, content protection, scope of activities, number of authors and books, publishing areas, formats, etc. Based on the case studies, the results presented focus on the geographical distribution of the analyzed companies, distribution of companies according to the year in which they were established, distribution of companies by activity, the number of different input formats supported by aggregation companies, a separate service of conversion, output formats supported by aggregation companies, distribution on platforms and in bookstores, content protection options, possibilities of editing content in the cloud, models of payment for services, and other identified services. Based on the results of the study, a conclusion is made that e-book aggregation as a business model exists and that its further development will show the extent to which it is sustainable.
Keywords: e-book aggregators; electronic publishing; e-book; academic publishing; e-book distribution platforms; e-book bookstores